Internal field measurements in Ni and Fe by the angular correlation rnethod. - Cisneros, J. I.; Liljegren, G.; Lindqvist, T.; Lopez Garcia, A. (Almqvist & Wiksells Boktryckeri, 1968)
Fil: Cisneros, J. I. Comisión Nacional de Energía Atómica; Argentina